Exome sequencing and functional analyses revealed CETN1 variants leads to impaired cell division and male fertility. Issue 4 (1st September 2022) - Sudhakar, Digumarthi V S; Phanindranath, Regur; Jaishankar, Shveta; Ramani, Anand; Kalamkar, Kaustubh P; Kumar, Umesh; Pawar, Asmita D; Dada, Rima; Singh, Rajender; Gupta, Nalini J; Deenadayal, Mamata; Tolani, Aarti Deenadayal; et al.
Abstract: Human spermatogenesis requires an orchestrated expression of numerous genes in various germ cell subtypes. Therefore, the genetic landscape of male infertility is highly complex. Known genetic factors alone account for at least 15% of male infertility. However, 40% of infertile men remain undiagnosed and are classified as idiopathic infertile men. We performed exome sequencing in 47 idiopathic infertile men (discovery cohort), followed by replication study (40 variants in 33 genes) in 844 infertile men and 709 controls using Sequenom MassARRAY® based genotyping. We report 17 variants in twelve genes that comprise both previously reported ( DNAH8, DNAH17, FISP2 and SPEF2 ) and novel candidate genes ( BRDT, CETN1, CATSPERD, GMCL1, SPATA6, TSSK4, TSKS and ZNF318 ) for male infertility. The latter have a strong biological nexus to human spermatogenesis and their respective mouse knockouts are concordant with human phenotypes. One candidate gene CETN1, identified in this study, was sequenced in another independent cohort of 840 infertile and 689 fertile men. Further, CETN1 variants were functionally characterized using biophysical and cell biology approaches. We demonstrate that CETN1 variant- p.Met72Thr leads to multipolar cells, fragmented nuclei during mitosis leading to cell death and show significantly perturbed ciliary disassembly dynamics. Whereas CETN1 –5′ UTR variant; rs367716858 leads to loss of a methylation site and increased reporter gene expression in vitro . We report a total of eight novel candidate genes identified by exome sequencing, which may have diagnostic relevance and can contribute to improved diagnostic workup and clinical management of male infertility.